Leaf Orientation Method as a Proxy for Sensing Nitrogen and Water Deficit in Tomato Plants - Yahia A. Othman; Daniel Leskovar (HortScience)
Precision field management and modeling crop growth requires precise, efficient, timely, nondestructive, and cost-effective measurements of structural component including leaf area index (LAI) and leaf orientation based on the foliage mean tilt angle (MTA), which is defined as the average leaf inclination angle of a canopy. Two experiments were carried out to investigate 1) the influence of different nitrogen (N) fertigation levels and 2) cycles of water deficit on leaf orientation (specifically, MTA) of young tomato (Solanum lycopersicum cv. Florida 47). N rates were 10, 50, 100, 200, and 300 mg·L−1 (mg N per liter of water) and irrigation treatments were well-watered and deficit irrigation. MTA was measured using the LAI-2200C Plant Canopy Analyzer. Across the experimental period, low N supply to leaves reduced the angle between leaf petiole and stem (high MTA) and produced plants with more erect leaves compared with N-sufficient plants. The MTA for the 10 mg·L−1–N treatment ranged from 54.3° to 73.6° and higher levels of N (50 to 300 mg·L−1–N) had MTA between 36.4° and 51.9°. Compared with lower N level (10 mg·L−1), LAI of tomato plants fertigated with a nutrient solution containing 300 mg·L−1–N increased by 3.6- to 4.9-fold across the study period. Similarly, canopy normalized difference vegetation index (NDVI) and leaf N% values at 300 mg·L−1–N were 2- to 3-fold higher than at 10 mg·L−1–N. However, MTA did not consistently differ across the 100 to 300 mg·L−1–N rates. In terms of water treatments, MTA of well-watered plants ranged from 32.3° to 40.5° whereas the same plants at water-deficit level had MTA between 45.7° and 51.8°. Although the relationship between MTA and canopy LAI, NDVI as well as leaf N was inconsistent or not significant under well-watered and water-deficit conditions, leaf gas exchange components (photosynthesis, stomatal conductance, and transpiration) showed a significant negative relationship (R2, 0.39–0.81, P < 0.001) with MTA. Overall, leaf orientation, specifically MTA, was modulated by N levels (highest at 10 mg·L−1; lowest at 300 mg·L−1–N) and cycles of water deficit and therefore, MTA determination hold promise as a nondestructive method to assess N and water deficit in young tomato plants.